Resting serum antioxidant status is positively correlated with peak oxygen uptake in endurance trained runners - Child, R. B.; Wilkinson, D. M.; Fallowfield, J. L. (The Journal of Sports Medicine and Physical Fitness, 1999)
BACKGROUND: This study tested the hypothesis that the ability to scavenge free radicals in serum was compromised in trained runners. METHODS: Experimental design: peak VO2, the ability to scavenge free radicals in serum and the plasma concentration of malondialdehyde (MDA) were assessed in 18 male runners. Participants: subject characteristics (mean +/- SEM) were height 1.77 +/- 0.01 m, mass 71.4 +/- 1.2 kg, age 31 +/- 1 years and weekly training distance 45 +/- 5 km.week-1. Measures: venous blood samples were collected at rest. Serum total antioxidant capacity (TAC) was determined using a chemiluminescent technique. This involved the oxidation of luminol, in a reaction catalysed by horseradish peroxidase. Serum antioxidant protection was quantified relative to a soluble vitamin E analogue (Trolox) and expressed as Trolox equivalents (Trolox Eq.). MDA was determined using a highly specific assay, using HPLC with fluorimetric detection. Peak VO2 was determined from expired gas measurements collected during an incremental running test on a motorised treadmill. Data were analysed using Pearson correlations. RESULTS: Serum TAC was 500 +/- 26 mumol Trolox Eq.l-1, with a plasma MDA concentration of 1.5 +/- 0.1 mmol.l-1 and serum urate concentration of 274 +/- 12 mmol.l-1. Peak VO2 was 63 +/- 1 ml.kg-1.min-1. Significant correlations were observed between peak VO2 and serum TAC (r = 0.365, p < 0.05); peak VO2 and serum urate (r = 0.463, p < 0.05) and serum urate and serum TAC (r = 0.807, p < 0.001). Plasma MDA and serum TAC were not significantly correlated (r = 0.026, p > 0.05). CONCLUSIONS: These data demonstrate that the ability to quench free radicals in serum in increased in relation to the maximum ability to consume oxygen, however this response does not appear to provide any additional protection against peroxidative damage at rest.